Możliwości wykorzystania porostów Hypogymnia physodes (L.) Nyl. do oceny wpływu przemysłu cementowego na środowisko przyrodnicze Białego Zagłębia = Possibilities of using lichen Hypogymnia physodes (L.) Nyl. to assess the impact of the cement industry on the natural environment of Białe Zagłębie - Kozłowski, Rafał. Autor; Ludew, Marta. Autor (IGiPZ PAN, 2025)
Air pollution in Europe, including Poland, still exceeds the levels recommended by the World Health Organization (WHO), despite numerous systemic and legal changes. This issue is not only a significant threat to human health but also has a broad impact on the natural environment. Air pollutants are mobile and can affect various environmental components over large areas. Harmful substances inhaled by humans lead to many diseases, negatively impact nature by disrupting photosynthesis, transpiration, and respiration processes, and cause the corrosion of metals and building materials (Degórska and Bartnicki, Abstract The cement industry in the Świętokrzyskie region, with plants in Nowiny, Ożarów, and Małogoszcz, plays a significant economic role, generating over 600 jobs. However, the activities of this industry are associated with the emission of dust and gases, which are a significant source of air pollution. The Lafarge Małogoszcz Cement Plant has been classified as one of the most environmentally burdensome plants in the region. Although data from recent years show a downward trend in emissions, these dusts still have a significant impact on the environment both locally and over greater distances through air migration (GUS, 2020; GIOŚ, 2023). To assess the condition of the natural environment under the influence of the cement industry, biomonitoring was used, which is based on analyzing the reactions of living organisms to pollutants. This method allows for the study of changes occurring in ecosystems at different levels: cellular, individual, and population. The lichen Hypogymnia physodes (L.) Nyl. was used in the studies, which is considered one of the best indicators of air sanitary conditions due to its ability to accumulate heavy metals proportionally to their concentrations in atmospheric dust (Jóźwiak, 2010; Traczewska, 2011). The studies were conducted in the so-called Białe Zagłębie area, covering about 50 km², with the Lafarge Małogoszcz Cement Plant at its center. The lichens were collected from the Borecka Forest, an area with minimal industrial influence, and exposed at measurement points around the cement plant. After three months of exposure, the samples were collected and analyzed in a laboratory, where the content of elements such as Pb, Cr, Co, Cu, Ni, Zn, Al, and Fe was measured. The studies showed that the cement industry significantly impacts air quality in the region, with the highest concentrations of pollutants near the cement plant. Hypogymnia physodes (L.) Nyl. lichens proved to be an effective bioindicator, allowing for precise monitoring and assessment of the environmental condition. The obtained data can be an important source of information for local authorities, governments, and environmental protection institutions, enabling effective actions to protect ecological systems. Knowledge about the impact of pollutants on the environment and the effectiveness of biomonitoring methods are crucial for conducting effective monitoring and environmental protection. The conclusions from the conducted studies may contribute to further development of technologies that reduce emissions and the introduction of stricter environmental standards, which in turn can improve air quality and the health of the region’s residents.
24 cm
Keywords: Geography